Rurbanomics for common prosperity: New approach to integrated urban-rural development - Chen, Kevin Z.; Mao, Rui; Zhou, Yunyi (Emerald Publishing Limited, 2023)
Challenges from the urban–rural disparity immensely burden the world's progress fulfilling Sustainable Development Goals and the goals' central promise, particularly for developing countries experiencing rapid structural change and urbanization. A knowledge gap lies between the epistemology of urban–rural disparity and the practice of integrated urban-rural development. This paper aims to provide a new approach to bridge the knowledge gap based on the recent Chinese experience.This qualitative research reviewed major economic and multidisciplinary studies regarding urban-rural development and the growth-equality tradeoff. Chinese experience is employed to showcase concrete challenges from the urban–rural disparity and how the proposed approach works for urban-rural integration.Theoretical and practical approaches with urban bias largely fail to counter the challenges. Building on China's recent practice probing beyond urban bias, IFPRI (2019) proposes the term rurbanomics with a highlight of equalized urban-rural economic partnership, whereafter Zhou and Chen (2021) enrich the term into a conceptual framework. This paper further improves rurbanomics as a new viable approach to integrated urban-rural development under the overarching goal of common prosperity. The approach prioritizes driving forces in the economic, demographic, eco-environmental, social institutional and technological aspects for the policy community to leverage. Long-term mechanisms are decerned to link urban-rural integration to common prosperity.China has leveraged ingredients of the rurbanomics approach in the political deployment to integrated urban-rural development. However, the application of this approach is yet to be adapted with local heterogeneities and live up to application's potential. Long-term mechanisms recommended by the rurbanomics approach will need to be carried out. Future improvements will need substantial theoretical extension and micro-level empirical studies.This paper streamlines the epistemological shreds regarding pursuits, challenges, global experiences and theoretical approaches of urban-rural development. The paper also develops rurbanomics to navigate urban-rural integration, Sustainable Development Goals and common prosperity. By decerning long-term mechanisms in the Chinese case accordingly, this paper provides clues for other economies to employ the new approach.